ANALYSIS OF MANDATORY WILLS AS A SOLUTION TO THE DISTRIBUTION OF INHERITANCE FOR ADOPTED CHILDREN FROM THE PERSPECTIVE OF ISLAMIC LAW AND ITS IMPLICATIONS FOR CHILDREN'S EDUCATION - Hafid Safrudin, Ahmad; Nurhidayati, Luluk (Mandeh : Jurnal Pendidikan Islam, 2025)
In the classical Islamic inheritance law system, the distribution of inheritance is based on the principle of faraidh, which only recognizes heirs through legal blood relations or marriage. As a result, adopted children do not receive inheritance rights from their adoptive parents, even though they have a very close social and emotional relationship. To address this imbalance, the concept of wajibah will emerged as a legal alternative, namely the granting of a portion of the obligatory inheritance to parties who are not entitled to inherit according to faraidh, including adopted children. This study aims to analyze the concept and legal basis of wajibah will from an Islamic legal perspective, examine its implementation in the Indonesian legal context, and assess the extent to which this concept can be a fair and effective solution in the distribution of inheritance for adopted children. This study uses a normative juridical method with a qualitative approach based on literature study. Data were collected through analysis of primary and secondary sources of the Qur'an, hadith, fiqh books, and the compilation of Islamic law. The results of the study indicate that although not recognized in classical fiqh, the mandatory will has been developed through ijtihad and codified in the KHI Article 209, which grants adopted children the maximum rights from the inheritance of their adoptive parents. However, its implementation still causes polemics, especially regarding the limitations of adopted children's rights, clarity of the legal basis, and considerations of justice for other legal heirs. This study concludes that the mandatory will is a compromise solution between the values ​​of social justice and sharia provisions, but its implementation requires legal clarity, proper socialization, and wise jurisprudential considerations to avoid new debates within the family. With the right approach, the mandatory will can be a legal instrument that bridges social needs with the principles of Islamic law.